Pseudo-ginsenoside Rh2 Induces Protective Autophagy in Hepatocellular Carcinoma HepG2 Cells - Zhang, Fuyuan; Xu, Huali; Xia, Rui; Yu, Ping; Li, Yuangeng; Yu, Xiaofeng; Sui, Dayun (Recent Patents on Anti-Cancer Drug Discovery, 2021)
Background: Pseudo-ginsenoside-Rh2 (pseudo-G-Rh2), a novel derivative of ginsenoside Rh2, is reported to exert a pro-apoptotic effect on various malignancies. However, whether this anti-cancer action of pseudo-G-Rh2 involves autophagy remains to be determined and explored. Objective: The objective of this study was to investigate the pseudo-G-Rh2-induced apoptosis and autophagy and the underlying mechanism. Methods: In the present study, the MTT assay was used for evaluating cell viability, and the lactate dehydrogenase (LDH) assay was performed to assess cell toxicity. Autophagy evaluation was performed using monodansylcadaverine (MDC) staining and transmission electron microscopy (TEM). The levels of autophagy-associated and apoptosis-associated proteins were determined using Western blotting. The Annexin V-FITC/propidium iodide (PI) assay was used to assess apoptosis. Results: The Annexin V-FITC/PI assay revealed that the percentage of apoptotic cells in HepG2 cells at concentrations 0, 20, 40, and 60 μM was 3.75%±1.37%, 5.70%±1.04%, 12.30%±2.10%, and 34.26%±4.73%, respectively. Pseudo-G-Rh2 was observed to significantly increase the expressions of BAX, cleaved-caspase-3, and cleaved-caspase-9, while it decreased the Bcl-2 expression. MDC and TEM analysis revealed that pseudo-G-Rh2 at concentrations 20, 40, and 60 μM significantly facilitated the accumulation of autophagosomes and autolysosomes within the HepG2 cells. Moreover, pseudo-G-Rh2 significantly increased the expressions of LC3 II/LC3 I and Beclin-1 and decreased the expression of p62. The Annexin V-FITC/PI assay also revealed that in comparison to the pseudo-G-Rh2 group, the concurrent treatment with pseudo-G-Rh2 and an autophagy inhibitor (CQ or 3-MA) significantly induced distinct apoptosis. In addition, pseudo-G-Rh2 activated AMPK and inhibited the PI3K/Akt/mTOR pathway in a concentration-dependent manner. Pseudo- G-Rh2 is similar to the current patents, which enhanced its anti-cancer activity by combining with autophagy inhibitors. Conclusion: Pseudo-G-Rh2 could induce protective autophagy in HepG2 cells, at least in part, via AMPK and the PI3K/Akt/mTOR pathway.
Keywords: mTOR